Modelling gyrosynchrotron emission from coronal energetic electrons in a CME flux rope - Husidic, E.; Wijsen, N.; Jebaraj, Immanuel C.; Vourlidas, A.; Linan, L.; Vainio, Rami; Poedts, S. (EDP Sciences, 2026)
Context. Solar flares and coronal mass ejections (CMEs) can accelerate electrons, causing bursts such as type IV emissions in the solar radio continuum. Although radio spectroscopy is a powerful diagnostic tool for the corona, the origin and mechanisms of type IV bursts remain uncertain. In situ measurements can occasionally shed some light on these mechanisms, but they are limited in space and time. Sophisticated numerical modelling offers the best approach to improve our understanding of the physical processes underlying particle dynamics and radio emission. Aims. This research examines type IV radio bursts, exploring the effects of various electron distribution properties and CMEs on their generation and characteristics. To transcend idealised assumptions, we employed realistic anisotropic electron distributions - obtained from particle transport simulations within complex magnetohydrodynamic (MHD) environments - as input for radio emission models. Methods. We used the three-dimensional coronal MHD model COCONUT to generate coronal background configurations, including a CME modelled as an unstable modified Titov-D & eacute;moulin magnetic flux rope (MFR). These MHD simulations were used by the PARADISE particle transport code, which injects energetic electrons into the MFR and tracks their evolution. Finally, we fed the electron distributions and solar wind parameters into the Ultimate Fast Gyrosynchrotron Codes to compute radio emission along lines of sight. Results. Electrons injected close to the flux rope's central axis remained largely confined, producing a gyrosynchrotron emission spectrum resembling observed type IV characteristics. Varying observer positions, CME properties, and spectral indices of the electron energy distributions modified the intensities and durations of the observed bursts. The strongest gyrosynchrotron emission was observed as originating from the CME flanks. Conclusions. Our results indicate that gyrosynchrotron emission is the major component in type IV spectra, although additional contributors cannot be ruled out.